The effect of applying an information guide about obesity on weight gain in pregnant women - عصفورا, جميلة; عيسى عبود دونا ,; عفاف عيسى نظام, (Latakia University Journal -Medical Sciences Series, 2023)
Excessive and improperly controlled weight gain during pregnancy has negative effects on pregnancy and its outcomes. Women's knowledge about balanced diet and physical activity plays an important role in controlling weight gain and preventing excessive weight gain. Therefore, the current experimental study aims to investigate the effect of applying an obesity information guide on weight gain in pregnant women. The sample included 200 pregnant women from the Maternity and Children Hospital in Lattakia, who were randomly divided into two groups: an experimental group that received the information guide and a control group that received routine care at the hospital. Data were collected using a tool developed by the researcher. The results showed the effectiveness of applying the obesity information guide in improving body mass index values in pregnant women compared to those who did not receive the guide. The study recommends the adoption of the information guide by nurses during the provision of nursing care to pregnant women, educating them on how to apply it, and conducting further research on the effect of applying an online information guide on weight gain during pregnancy.